Evaluation of hydrocarbon source rock potential: Deep marine shales of Belaga Formation of Late Cretaceous-Late Eocene, Sarawak, Malaysia - Ahmed, N. (Elsevier B.V., 2021)
In the Sibu-Tatau region of Sarawak, the Belaga Formation (Late Cretaceous- Late Eocene turbidites) is interpreted in relation to a submarine fan model deposited in the extinct ocean basin of the proto-South China Sea. A number of clastic rocks, which include sandstone, siltstone, mudstone, and black shale, define the formation. While it is considered one of the Rajang group's extensive and well-studied formations, yet no comprehensive studies have been carried out on the shales in Sarawak, Malaysia, to interpret their importance as a source rock to oil and gas fields. The present study highlights the prominent lithofacies in addition to the detailed source rock characterization of each member of Belaga Formation to discuss the potential source rock intervals present in these Cretaceous to Eocene rock units. Four major types of shales and mudstones facies were observed in the field, i.e. (i) Variegated colored shale facies (VSF), (ii) Black âPaperyâ shale facies (BSF), (iii) Gray to black mudstone facies (GMF), (iv) Silty/sandy shale facies (SSF). They show hemipelagic settling in a calm environment to turbiditic deposition at levees as well as distal lobe depositional environment. In this study primary geochemical studies such as Rock-Eval pyrolysis and Total Organic Carbon (TOC) analysis were used to classify the thermal maturity, organic matter richness, and kerogen type of the studied shales. Forty-six selected shale samples were studied from the formation, including samples from members of the Layar (Upper Cretaceous), Kapit (Paleocene to Early Eocene), Pelagus (Early to Middle Eocene), Metah (Middle to Late Eocene) and Bawang (Eocene). The shales of Belaga Formation typically display low to moderate source rock potential, which is obvious by low TOC contents between 0.14 wt and 7.22 wt (average of about 2.97 wt) and show a wide range of maturity (immature to over mature) evident from very low to very high Tmax values ranging from 293 Â°C to 610 Â°C. The results show that the kerogen is of type IV, with some units can be potential sources of gas. Â© 2020 The Author(s)